Un espace de dialogue sur les gestes professionnels en établissement scolaire - Caroline STREHL; Sylvie MOUSSAY (Éducation et Socialisation)
This article presents a study analyzing discussions between teachers and school life office staff. These discussions took place in a junior high school. This study is part of a study program within the field of cultural historical activity theory (Clot, 2008; Leontiev, 1984; Vygotsky, 1997, 2003). The analysis enabled to highlight the way exchanges were conducted through videos and audio extracts showing the way activities initiate collective thoughts on work “gestures”. During these exchanges, gestures -which were until now unseen (such as the fluttering of a butterfly’s wings) were subjects of repetitions and transformations by the teachers according to the signification expressed by teachers referring to the professional genra while engaging into stylistic comparisons, a necessary step towards the appropriation of the gesture. The discussion bears on the interest of dialog spaces in schools, since it can sustain the development of teachers’ activity.